2014
DOI: 10.1292/jvms.14-0177
|View full text |Cite
|
Sign up to set email alerts
|

Unpredictable Chronic Stress-Induced Reproductive Suppression Associated with the Decrease of Kisspeptin Immunoreactivity in Male Mice

Abstract: Environmental stress affects various parts of mammals typically through the circulation of stress hormones. It has been identified as one of the possible reasons for male reproductive difficulties, but the complex mechanisms responsible for stress-induced reproductive suppression are poorly understood. Here, we examined the relationship between chronic environmental stress and hypothalamic kisspeptin, a recently discovered upstream regulator of the reproductive endocrine feedback system. We studied male mice u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…In agreement with the findings of our aforementioned study, the administration of LPS decreased hypothalamic Kiss1 mRNA expression and kisspeptin immunoreactivity, and the co-administration of kisspeptin partially restored serum LH levels in female rats [76]. In addition, other kinds of stress, such as psychosocial, unpredictable chronic (six randomly assigned stressors), and hypoglycemic stress, also reduced hypothalamic Kiss1 mRNA expression and kisspeptin neuron activity [77][78][79]. Some studies have also evaluated the intermediate factors that transfer stress signals to kisspeptin neurons.…”
Section: The Roles Of Kisspeptin In Stress-induced Hpg Axis Dysfunctionsupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with the findings of our aforementioned study, the administration of LPS decreased hypothalamic Kiss1 mRNA expression and kisspeptin immunoreactivity, and the co-administration of kisspeptin partially restored serum LH levels in female rats [76]. In addition, other kinds of stress, such as psychosocial, unpredictable chronic (six randomly assigned stressors), and hypoglycemic stress, also reduced hypothalamic Kiss1 mRNA expression and kisspeptin neuron activity [77][78][79]. Some studies have also evaluated the intermediate factors that transfer stress signals to kisspeptin neurons.…”
Section: The Roles Of Kisspeptin In Stress-induced Hpg Axis Dysfunctionsupporting
confidence: 89%
“…As a result, it was found that both the central administration of CRH and the peripheral administration of corticosterone reduced hypothalamic Kiss1 mRNA expression and kisspeptin neuron activity in female rats and mice, indicating that activation of the HPA axis is involved in the stressinduced suppression of the kisspeptin system [77,80]. Interestingly, relatively severe stress protocols were used in these studies; i.e., high-dose LPS (1-5 mg/kg) or repeated LPS administration protocols (three consecutive injections at 24-h intervals), to evaluate the effects of immune stress [75,76,81,82], and chronic (once per day for four weeks) or combined (restraint and isolation) protocols were used to evaluate the effects of unpredictable and psychosocial stress [78,79]. Similarly, we found that a subseptic dose (500 μg/kg) of LPS did not affect hypothalamic Kiss1 mRNA expression in female rats, indicating that only chronic or severe stress affects the kisspeptin system [81,82].…”
Section: The Roles Of Kisspeptin In Stress-induced Hpg Axis Dysfunctionmentioning
confidence: 99%
“…All gels were weighed daily to estimate the amounts of the putative CTD exposure. In the four stress groups, the mice were subjected to an unpredictable chronic stress procedure as described in our earlier report [ 14 ] with some modifications. Briefly, the following six stressors were used: 5 min forced swimming in water at room temperature (RT), 24 hr food and water deprivation, continuous overnight illumination, 30 min horizontal cage shaking (80 rpm), 24 hr switching of cagemates (being housed with another mouse) and 24 hr wet bedding.…”
Section: Methodsmentioning
confidence: 99%
“…After administration of PMSG/hCG to induce superovulation, we found that moderate or severe stress mice stimulated by CUMS had a decreased ovarian response and oocyte development potential. Tetsushi HIRANO et al also reported a reproductive suppression male mice model induced by CUMS [ 30 ]. This negative outcome resulted from multilevel interactions among the hypothalamic-pituitary- adrenal axis and the hypothalamic-pituitary-gonadal axis, the immune system, and the autonomic nervous system.…”
Section: Discussionmentioning
confidence: 99%